Hadronic gas models in particle production and phase transitions - Weber, Götz Mathias (Department of Physics, 2016)
In this work the methods of exact quantum number conservation in statistical mechanics are discussed and applied to the field of high energy nucleus-nucleus collisions. Various types of hadronic gas models are discussed as well as their merits and restrictions. Attempts to construct a phenomenological equation of state for nuclear matter are discussed in the context of the phase transition from hadronic matter to the quark-gluon plasma (QGP).